Developing a core outcome set for the treatment of pregnant women with pregestational diabetes—a study protocol - Kgosidialwa, Oratile (Trials, 2020)
BACKGROUND: Pregestational diabetes mellitus (PGDM) is associated with adverse pregnancy outcomes including increased rates of caesarean section birth, macrosomia, congenital malformation, prematurity, admission to the neonatal intensive care unit and stillbirth. As a result, there has been an increase in interventions to improve outcomes in both mother and infant. To date, meaningful comparisons between these studies are limited due to heterogeneity in outcome selection and reporting. The aim of this study is to develop a core outcome set (COS) for randomised controlled trials evaluating the effectiveness of interventions for the treatment of pregnant women with PGDM. METHODS: The study consists of three steps. The first step is a systematic review of the literature to assess outcomes reported in randomised controlled trials assessing the effectiveness of interventions for the treatment of pregnant women with PGDM. The second step is a three round, online Delphi survey to prioritise these outcomes. In this step, stakeholders (including women with PGDM, healthcare workers, researchers and policymakers) will be asked to rank the importance of outcomes for inclusion in the COS using a 9-point Likert type scale. Outcomes that meet the inclusion criteria after completion of the Delphi surveys will be brought to the consensus meeting. The consensus meeting will be the third and final step, where the COS will be finalised. The consensus meeting will include members from each stakeholder group. DISCUSSION: This paper describes the process used to develop a COS for the reporting of studies evaluating the effectiveness of interventions in pregnant women with PGDM. The COS will enable greater comparison between and information synthesis across RCTs in the treatment of PGDM. In addition, this COS will also help improve trial reporting and minimise research waste by prioritising the collection and reporting of outcomes that matter to all relevant stakeholder groups. TRIAL REGISTRATION: This COS has been registered with the Core Outcome Measures in Effectiveness Trials (COMET) initiative (http://www.comet-initiative.org/studies/details/1425) on the 4th of November 2019. The systematic review component of this study has also been registered with the International Prospective Register of Systematic Reviews (PROSPERO) (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020173549). SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s13063-020-04910-1.